A Proposed Training Program for Developing Verbal Imitation Skills among Children with Autism Spectrum Disorder - Isa Ahmed Al-Slaim, Maisaa (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
This research aimed to test the effectiveness of a training program to develop the skills of verbal imitation in a sample of children with autism spectrum disorder. To achieve the aims of the research, two tools were applied in the study, prepared by the researcher, namely: (Verbal Imitation Skills Scale, and Training Program). The study sample consisted of twenty children with autism spectrum disorders whom was enrolled in Al-Awj Center for Autism in the Irbid, Jordan, aged 5- 8 years. Data collecting from the application of the two tools were analyzed by using the non-parametric statistics. The study showed the following results: there are significant differences in verbal imitation skills after the application of the program in favor of the experimental group. Also, there are significant differences in verbal imitation skills of the experimental sample in favor of the post measurement. In the light of the research findings, a number of recommendations are suggested.